HARMONI PENGABDIAN: MERAJUT ASA LEWAT LITERASI DAN AKSI SOSIAL DI SERAPUH - Nicholas Simbolon; Deva Gultom; Maria Manurung; Nomi Tamba; Kasih Sitinjak; Paskah Sitompul; Samuelson Damanik; Ezra Napitu; Lilis Napitu; Eli Ginting; Radode K simarmata; Melisa Novra Hutabarat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Community service activities are one of the concrete forms of contribution in improving the quality of education and social welfare of society. The program “Harmony of Service: Weaving Hope through Literacy and Social Action in Serapuh” aims to increase literacy awareness while fostering social concern within the community, especially among children and adolescents. This activity was carried out through various programs such as learning assistance, strengthening reading culture, and social activities involving the local community. The methods used included a participatory approach through socialization, mentoring, and interactive educational activities. The results of the program indicate that these activities were able to increase participants’ interest in reading, broaden their knowledge, and strengthen social relationships between university students and the community. In addition, social action activities also encouraged the growth of mutual cooperation and concern for the surrounding environment. Therefore, this community service program is expected to become an initial step in building a more literate, caring, and empowered society through collaboration between students and the community